2020
DOI: 10.1007/s11469-019-00213-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Recreational Online Activities in School-Based Screen Time Sedentary Behaviour Interventions for Adolescents: A Systematic and Critical Literature Review

Abstract: Sedentary behaviours are highly associated with obesity and other important health outcomes in adolescence. This paper reviews screen time and its role within school-based behavioural interventions targeting adolescents between the years 2007 and 2019. A systematic literature review following PRISMA guidelines was conducted across five major databases to identify interventions targeting screen time-in addition to TV/DVD viewing. The review identified a total of 30 papers analysing 15 studies across 16 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 218 publications
1
19
0
5
Order By: Relevance
“…Instead, a monetized subscription-based business model offering commercial-free and data protected social exchanges could potentially find greater support if social media operators and regulators went beyond safeguarding data protection and rights of minors, into encouraging a more socially responsible social media business model. Equally with corporate social responsibility (CSR) initiatives in other industries – i.e., the food and beverage industry, which has endorsed healthier eating habits or more environmentally friendly agricultural and trading conditions ( World Health Organization, 2004 ) – the greater promotion of user rights and representation, the reduction of poverty, social inequality, and greater access to media literacy, the prevention of sedentary lifestyles and obesity, radicalization, and the encouragement of social entrepreneurship could be just a few of the social media industry’s CSR initiatives for a healthier platform ecosystem ( Afridi and Joseph Rowntree Foundation, 2011 ; Paus-Hasebrink et al, 2019 ; Throuvala et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a monetized subscription-based business model offering commercial-free and data protected social exchanges could potentially find greater support if social media operators and regulators went beyond safeguarding data protection and rights of minors, into encouraging a more socially responsible social media business model. Equally with corporate social responsibility (CSR) initiatives in other industries – i.e., the food and beverage industry, which has endorsed healthier eating habits or more environmentally friendly agricultural and trading conditions ( World Health Organization, 2004 ) – the greater promotion of user rights and representation, the reduction of poverty, social inequality, and greater access to media literacy, the prevention of sedentary lifestyles and obesity, radicalization, and the encouragement of social entrepreneurship could be just a few of the social media industry’s CSR initiatives for a healthier platform ecosystem ( Afridi and Joseph Rowntree Foundation, 2011 ; Paus-Hasebrink et al, 2019 ; Throuvala et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schools could also be trained to identify problem signs that may otherwise go undetected (when there is a sustained negative change on functional domains of life, such as school, academic work, activities or hobbies, and/or relationships with significant others and provide peer support networks for children at risk, and liaise with families, charities, and special services [i.e., the Child and Adolescent Mental Health Services (CAMHS) in the UK] at an early intervention stage—prior to referral. Within schools, environmental changes (i.e., engagement with short physical activity exercises during breaks, charity support work with after school activities) could be encouraged, which have been found to be beneficial in interventions tackling obesity [ 149 , 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…These impacts were viewed as needing to be addressed in media and mental health literacy (Kutcher et al, 2016) in line with recent policy changes in the United Kingdom supporting mental wellbeing in schools (Department for Education, 2020). Teacher perceptions expressed suggested that a supportive school environment with the collaboration of external mental health services were the pathways to primary prevention (Throuvala et al, 2019;Throuvala et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…School-based prevention and mental health literacy (Throuvala et al, 2019;Throuvala et al, 2020) have been suggested as important ingredients in supporting students' beneficial use of social media and embrace the positive outcomes in terms of learning and engagement (Stathopoulou et al, 2019) while reducing problematic screen time involvement and smartphone use (Subhash and Cudney, 2018;Rach and Lounis, 2021). In China, which has the highest number of smartphone users (Newzoo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation